Antiproliferative and apoptotic effect of tuna blood on human lung cancer A549 cells via p38 MAPKs and Akt pathway - Siraprapa Saetan; Wanida Sukketsiri; Pennapa Chonpathompikunlert; Wanwimol Klaypradit; Mantira Hawangjoo; Nujamee Ngasakul; Supita Tanasawet (Journal of King Saud University: Science, 2023)
Tuna blood has been reported the anti-inflammatory properties. However, the anticancer effects of tuna blood remain unelucidated. Therefore, this study investigated the anticancer effects of tuna blood against human non-small cell lung cancer (NSCLC) A549 cells and its potential mechanism of action. The amino acid profile presented in tuna whole blood freeze-dried (TWBF) and tuna blood cell freeze-dried (TRBF) were analyzed, and the antiproliferative effect was assessed by MTT assay. The nuclear staining, reactive oxygen species (ROS) generation, and mitochondrial membrane potential (MMP) were examined by Hoechst/PI staining, DCFHDA assay, and JC-1 staining. The expression of apoptosis-related proteins and the involvement of p38 MAPKs and Akt signaling were evaluated by western blotting. TWBF and TRBF inhibited the proliferation of lung cancer A549 cells with IC50 values of 354.97, 141.31 µg/mL, respectively. TRBF revealed more efficacy of cell proliferation inhibition than that of TWBF. The percentage of apoptotic cell death after treatment with 100 µg/mL TRBF was 35.95%. The increase in the ROS production and the disruption of MMP were also detected. At a mechanistic level, the exposure of TRBF to A549 cells showed an increase of the Bax/Bcl2 ratio and subsequently activated the proteolytic activity of caspase-3. TRBF administration induced apoptosis through the downregulation of protein kinase B (Akt) and upregulation of p38 MAPK. These findings indicate TRBF inhibits lung cancer cell proliferation and mediates apoptosis signaling, suggesting a promising chemotherapeutic candidate target NSCLC.